4(k-9)+18=6

Simple and best practice solution for 4(k-9)+18=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(k-9)+18=6 equation:


Simplifying
4(k + -9) + 18 = 6

Reorder the terms:
4(-9 + k) + 18 = 6
(-9 * 4 + k * 4) + 18 = 6
(-36 + 4k) + 18 = 6

Reorder the terms:
-36 + 18 + 4k = 6

Combine like terms: -36 + 18 = -18
-18 + 4k = 6

Solving
-18 + 4k = 6

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 4k = 6 + 18

Combine like terms: -18 + 18 = 0
0 + 4k = 6 + 18
4k = 6 + 18

Combine like terms: 6 + 18 = 24
4k = 24

Divide each side by '4'.
k = 6

Simplifying
k = 6

See similar equations:

| -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x | | 2x+6/x+3 | | 25X+6-27X=5-9 | | 3(z-2)=2(z+7) | | -7(3n+2)=-8n+38 | | 7+36=-11 | | 10x-12y=2 | | 5.3m-6=-27.2 | | 5y+6=4y-7 | | .16(12)+.04x=.08(24+x) | | n-4-9=0 | | 2.3f=9.2 | | -4y+-12=2y-14 | | -9(x-1)=9-9x | | 10=7x-6 | | 2-2a=-3(-6+6a)+8a | | -5+9n+6=0 | | -12abc+2abc-8A= | | 7x-5y+3x-2y= | | -3(2s-5)-15=-2(6s+4)-2 | | u+3=9 | | 5a*5ab= | | 2+y+1=5 | | 4(2x+-1)+6=8x+-4 | | 4(2x+-1)+6=8x+-3 | | 3/7x42/14 | | 1.80=n/100(30) | | n+4-9-5n=0 |

Equations solver categories